Chapter New Radiation Pattern-Reconfigurable 60-GHz Antenna for 5G Communications - Abdullah, Abdulkareem S. (InTechOpen, 2019)
Reconfigurable beam steering using circular disc microstrip patch antenna with a ring slot is proposed. The overall dimension of the antenna is 5.4 × 5.4 mm2 printed on 0.504 mm thick, RT5870 substrate with relative permittivity 2.3 and loss tangent 0.0012. The designed antenna operates at the expected 60 GHz 5G frequency band with a central coaxial probe feed. Two NMOS switches are utilized to generate three different beam patterns. Activating each switch individually results in a 70° shift in the main beam direction with constant frequency characteristics. The power gain is 3.9-4.8 dB in the three states of switch configurations. Simulated results in terms of return loss, peak gains and radiation pattern are presented and show good performance at the expected 60 GHz band for 5G applications.